Pichia pastoris Mediated Digestion of Water-Soluble Polysaccharides from Cress Seed Mucilage Produces Potent Antidiabetic Oligosaccharides - Imdad Ullah Khan; Yusra Jamil; Aiman Khan; Jalwa Ahmad; Amjad Iqbal; Sajid Ali; Muhammad Hamayun; Anwar Hussain; Abdulwahed Fahad Alrefaei; Mikhlid H. Almutairi; Ayaz Ahmad (MDPI AG, 2024)
Diabetes mellitus is a heterogeneous metabolic disorder that poses significant health and economic challenges across the globe. Polysaccharides, found abundantly in edible plants, hold promise for managing diabetes by reducing blood glucose levels (BGL) and insulin resistance. However, most of these polysaccharides cannot be digested or absorbed directly by the human body. Here we report the production of antidiabetic oligosaccharides from cress seed mucilage polysaccharides using yeast fermentation. The water-soluble polysaccharides extracted from cress seed mucilage were precipitated using 75% ethanol and fermented with Pichia pastoris for different time intervals. The digested saccharides were fractionated through gel permeation chromatography using a Bio Gel P-10 column. Structural analysis of the oligosaccharide fractions revealed the presence of galacturonic acid, rhamnose, glucuronic acid, glucose and arabinose. Oligosaccharide fractions exhibited the potential to inhibit α-amylase and α-glucosidase enzymes in a dose-dependent manner in vitro. The fraction DF73 exhibited strong inhibitory activity against α-amylase with IC50 values of 38.2 ± 1.12 µg/mL, compared to the positive control, acarbose, having an IC50 value of 29.18 ± 1.76 µg/mL. Similarly, DF72 and DF73 showed the highest inhibition of α-glucosidase, with IC50 values of 9.26 ± 2.68 and 50.47 ± 5.18 µg/mL, respectively. In in vivo assays in streptozotocin (STZ)-induced diabetic mice, these oligosaccharides significantly reduced BGL and improved lipid profiles compared to the reference drug metformin. Histopathological observations of mouse livers indicated the cytoprotective effects of these sugars. Taken together, our results suggest that oligosaccharides produced through microbial digestion of polysaccharides extracted from cress seed mucilage have the potential to reduce blood glucose levels, possibly through inhibition of carbohydrate-digesting enzymes and regulation of the various signaling pathways.